Human Resource Management Problems in Chinese Family-owned Company: A Study in Yuchun Company - QIN, Siyu (2017)
With the quick development family-owned companies, there is an increasing interest shown towards this type of company. However, most researches are usually based on the American or European family-owned companies. Thus, more international and deep case studies especially in Asian family-owned company are needed. Moreover, only a few researches focus on finding problems and deep reasons in Chinese family-owned companies’ human resource management system. This dissertation uses interviews and fieldwork to demonstrate problems and some deep reasons in Chinese family-owned companies’ human resource management system. It is relied on a single case study of a family-owned company in Shenzhen China. The research findings are extracted from the data collected in 25-day fieldwork and interviews. The results show that in the company, founder dose has conflicts with his daughter and the succession is also a problem that founder has to face. In terms of employees’ motivation, most employees are unsatisfied with current motivation mechanism, and major problems for motivation appears in 4 aspects: improper view of people usage, irregular management system, useless performance appraisal and imperfect motivation methods. The major reasons for these problem are Chinese traditional culture and organization structure. The main contribution of this dissertation is providing a deep investigation in Chinese family-owned company’s human resource management system and some problems and deep reasons are found so that other Chinese family-owned companies can learn from it and take some measures to deal with their own problems so that better development of Chinese family-owned companies can be achieved.